Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai di Kantor Dinas Pendidikan Daerah Provinsi Sulawesi Utara - Mamesah, Merlinda; Itje Pangkey; Abdul R. Dilapanga (Indra Institute Research & Publication, 2025)
This study aims to analyze the influence of the work environment and work discipline on employee job satisfaction at the Regional Education Office of North Sulawesi Province. The research employed a quantitative approach, utilizing primary data collected through questionnaires. The findings indicate that the work environment has a significant partial effect on employee job satisfaction. Additionally, work discipline also significantly influences job satisfaction. Simultaneously, the work environment and work discipline collectively have a significant impact on employee job satisfaction at the office. These findings highlight that fostering a conducive work environment and enforcing effective work discipline can enhance employee satisfaction. This research provides valuable insights into human resource management, particularly in creating a positive workplace atmosphere and improving employee discipline levels to achieve optimal job satisfaction